ANALISIS PERBANDINGAN PERAN KEPEMPIMPINAN TEKNOLOGI INFORMASI PADA PERUSAHAAN NOKIA DAN SAMSUNG - A. Teguh S, D. Christina Pasaribu, E. David Saragih, P. Syukur Sumantri (Institut Bisnis dan Informatika Kwik Kian Gie, 2018)
Nokia and Samsung compete in the same business area, it is cellular phone. The difference of them is Nokia released cellular phones throughout the world earlier and received the title of being largest cellular phone market's ruler in the world for 14 years until Samsung ended Nokia's dominance and got the title in 2012. This paper was aimed to analyze the comparison of Nokia and Samsung's information technology leadership roles during the company's business story to achieve title of the cellular phone market's ruler, especially during Samsung's rise and Nokia's fall. This paper uses literature study method on books, journals, and articles which related to historical events regarding Nokia and Samsung and the role of information technology (IT) leadership at Nokia and Samsung. The results obtained from this paper are that Samsung managed to take advantage of IT's leadership role in the strategic quadrant, while Nokia's IT leadership role was only in the turnaround quadrant. The quadrant is determined from the approach and dynamics of information technology leadership that occurred at Nokia and Samsung.Â Keywords: Nokia, Samsung, Information technology leadership role, Dynamics of information technology leadership